2020
DOI: 10.3389/fmicb.2020.543589
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Storms on Legionella pneumophila in Cooling Tower Water, Implications for Human Health

Abstract: At the U.S. Department of Energy’s Savannah River Site (SRS) in Aiken, SC, cooling tower water is routinely monitored for Legionella pneumophila concentrations using a direct fluorescent antibody (DFA) technique. Historically, 25–30 operating SRS cooling towers have varying concentrations of Legionella in all seasons of the year, with patterns that are unpredictable. Legionellosis, or Legionnaires’ disease (LD), is a pneumonia caused by Legionella bacteria that thrive both in man-made water distribution system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…Contextual information about the cooling tower is also important. For example, the meteorological conditions such as warm temperature, low winds, high humidity (Russo et al , 2018) or storms that may increase the risk of legionella proliferation and diffusion, even if biocides are used (Brigmon et al , 2020). It is now clear that climate change will escalate the problem of legionnaires’ disease and call for action from governments, academics and private organizations (Walker, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Contextual information about the cooling tower is also important. For example, the meteorological conditions such as warm temperature, low winds, high humidity (Russo et al , 2018) or storms that may increase the risk of legionella proliferation and diffusion, even if biocides are used (Brigmon et al , 2020). It is now clear that climate change will escalate the problem of legionnaires’ disease and call for action from governments, academics and private organizations (Walker, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, temperatures in the South reach Legionella -promoting temperatures, which also increase cooling tower use, earlier in the year than in the Northeast or Midwest, which might explain why the LD season begins first in the South ( 33 ). Furthermore, hurricane-produced rainfall increased during 1998–2016 ( 34 ), and hurricanes have been associated with elevated concentrations of Legionella bacteria in cooling towers and surface water ( 35 , 36 ). Travel is also a cyclical risk factor for LD but does not appear to influence seasonality; seasonal patterns for travel-associated cases were nearly identical to those for non–travel-associated cases during 2015–2016 ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Freshwater is considered the major reservoir for the pathogenic Legionella pneumophila ( Boamah et al, 2017 ). However, Legionella is often studied in man-made water systems, such as cooling towers ( Brigmon et al, 2020 ), due to the thermophily of the pathogen L. pneumophila ( Lesnik et al, 2015 ). Even though it is known that Legionella exist in freshwater and have cold-adapted variants ( Lesnik et al, 2015 ), few studies have reported their occurrence in natural aquatic environments, such as in lakes, rivers, and estuaries ( Carvalho et al, 2007 ; Parthuisot et al, 2010 ; Shimada et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%